Explicit Parallel Instruction Computing (International Journal of Engineering and Computer Science, 2017)
VLIW (Very Long Instruction Word) machines are highly parallel ILP (Instruction Level Parallelism) based architectures that offer an alternative to scalar sequential architectures like CISC/RISC. With VLIW, the burdensome task of dependency checking by hardware logic at run time is removed and delegated to the compiler. HP and Intel introduced a new style of instruction set architecture called EPIC (Explicitly Parallel Instruction Computing), and a specific architecture called the IPF (Itanium Processor Family). EPIC is like VLIW, with extra cache prefetching instructions. EPIC combines the capabilities of both Superscalars processors and VLIW processors. Through this paper, we will try to understand the characteristics of EPIC processors which make them distinguishable